Study into optimizing the temperature regime for the reduction of Fischer–Tropsch synthesis catalysts - I. G. Solomonik; V. Z. Mordkovich; A. S. Gorshkov (Тонкие химические технологии)
Objectives. The work set out to investigate the potential for developing an efficient cobalt catalyst for Fischer–Tropsch synthesis through low-temperature activation by reduction in hydrogen directly in the synthesis reactor. Such an approach could be used to enhance the overall economic viability of the process.Methods. The reduction of a zeolite-containing catalyst with a heat-conducting system based on thermally expanded graphite in an aluminum oxide binder carrier was investigated within the temperature range of 300–400°C. The degree of reduction of the powdered catalyst (to remove diffusion restrictions) was determined by conducting temperature-programmed reduction subsequent to the reduction at the studied temperature. Autosorb-1C and STA 449 F1 (Netzsch, Germany) devices were used in this work. The identified activation mode was evaluated at a Fischer–Tropsch synthesis pilot plant at INFRA (Moscow, Russia).Results. Activity and selectivity values of the catalyst reduced at 325°C are determined from chromatographic analysis of the products. Low-temperature (325°C) reduction is shown to provide better catalytic parameters due to the implementation of a larger number of highly dispersed cobalt-oxide structures fixed on the hydrated surface of the support, resulting in the appearance of Coδ+ centers with increased activity and selectivity for the formation of C5+ hydrocarbons.Conclusions. The described catalytic system demonstrates the potential advantages in carrying out reductive activation in hydrogen at 325°C as opposed to the conventional 400°C. This approach markedly enhances the economic viability of the entire process, particularly for small-scale installations, due to the reduced thermal stability of the steel material reactor.